A novel mutation of MSX1 inherited from maternal mosaicism causes a severely affected child with nonsyndromic oligodontia. (30th August 2019) - Ma, Tengfei; Liu, Yi; Zhao, Xiaoxue; Wu, Jing; Wang, Huijuan; Chen, Jing; Liu, Peiwen; Zhang, Xu; Zhang, Xiangyu
Abstract: Mutations of MSX1 have been associated with nonsyndromic hypodontia. To seek the causal gene mutation sites in a family with nonsyndromic oligodontia, whole‐exome sequencing (WES) was performed to seek the causative locus of the family. The candidate mutation was further identified by Sanger sequencing afterward. Two mutations of MSX1 were found both in the proband and her mother. One novel heterozygous missense mutation (c.C667G, p.R223G) of MSX1 inherited from the asymptomatic mother with mosaic mutation was located in the highly conserved fragment of exon 2. The other was a synonymous mutation (c.C348T, p.G116G) in exon 1, which had been reported. The novel maternal heterozygous missense mutation (c.C667G, p.R223G) was likely to be the major reason for nonsyndromic oligodontia in the family. This is the first mosaic variant that has been recorded of the MSX1 gene. Our study expands the phenotype–genotype correlation associated with MSX1 variants. Our study also suggests that the determination of the mosaicism is essential for precise genetic counseling if a disease appears to arise de novo.